Analyse comparative du rôle des normes et pratiques journalistiques à la télévision dans la couverture de la campagne électorale fédérale canadienne de 1997 - Agnieszka Dobrzynska (Communication)
What are the journalistic standards and practices in the coverage of an election campaign ? Do journalists apply the standards to which they subscribe in the abstract ? This article compares the standards and practices of journalists from two networks, one private, one public, during the 1997 federal election campaign. It shows that journalists who work under strict professional standards laid out by their bosses do not produce coverage which is different from those who work under no such strictly spelled out guidelines. The article analyses the reasons for the incompatibility between standards and practices.